THE IMPLEMENTATION OF AUKUS IN AMERICAN FOREIGN POLICY IN THE INDO-PACIFIC - Ulung, Alessandro Kurniawan (Rubikon : Journal of Transnational American Studies, 2025)
This research aims to examine the implementation of AUKUS in the Indo-Pacific. AUKUS is a trilateral security partnership between the United States, the United Kingdom, and Australia, to enable Australia to acquire nuclear-powered submarines. The transfer of the submarines under AUKUS raised tensions between the U.S. and China and some Southeast Asian countries. They slammed the U.S., claiming the partnership could destabilize security in the Indo-Pacific. Despite these rising tensions, the U.S. continues to advance AUKUS. This research seeks to explore the implementation of AUKUS, discussing how the American government achieves the objective of the partnership. This research uses Graham Allison's Rational Actor Theory and employs a qualitative method to examine the calculation of costs and benefits behind the establishment of AUKUS and to analyze its implementation, with interviews and a literature review in place. This research finds that the U.S. is gradually implementing AUKUS by initiating training programs and joint military exercises aimed at preparing Australian personnel to operate nuclear-powered submarines effectively. Despite growing protests against AUKUS, the U.S. remains committed to maintaining this partnership due to its strategic benefits: enhancing power projection, expanding influence, and strengthening deterrence in the Indo-Pacific. This research contributes to enriching literature on AUKUS.